2019
DOI: 10.1108/wjstsd-05-2018-0048
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic relationship between embodied and operational impacts of buildings

Abstract: Purpose Buildings and their construction activities consume a significant proportion of mineral resources excavated from nature and contribute a large percentage of CO2 in the atmosphere. As a way of improving the sustainability of building construction and operation, various sustainable design appraisal standards have been developed across nations. Albeit criticism of the appraisal standards, evidence shows that increasing sustainability of the built environment has been engendered by such appraisal tools as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A sustainable environment seeks to improve human welfare by protecting the sources of raw materials used for human needs and mitigating harm to humans (Ajayi, Oyedele, & Jamiu, 2019;Ilhan & Banu Yobas, 2019;Razali, 2018;Zaid & Zainon, 2019). The environment perspective or also known as the ecological dimension is mostly illustrated as global warming prevention.…”
Section: Environment Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…A sustainable environment seeks to improve human welfare by protecting the sources of raw materials used for human needs and mitigating harm to humans (Ajayi, Oyedele, & Jamiu, 2019;Ilhan & Banu Yobas, 2019;Razali, 2018;Zaid & Zainon, 2019). The environment perspective or also known as the ecological dimension is mostly illustrated as global warming prevention.…”
Section: Environment Perspectivementioning
confidence: 99%
“…Masalskyte, Andelin, Sarasoja, & Ventovuori (2014) recount that the social dimension of a sustainable building includes a healthy and comfortable working environment, employee engagement to sustainability-related activities, promotion of employee satisfaction, and working efficiency. Other than that, most research reveals that sustainable buildings manifest social benefits through improved safety and health (Lu & Taylor, 2018) that directly enhance the quality of life (Ajayi et al, 2019) and promotes a healthy life (Zhang, Kang, & Jin, 2018). Eichholtz & Kok (2018) and Rogerson (2014) experience reduced number of employee sick leave days and reduced staff turnover.…”
Section: Social Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with Kamaruzzamana et al, 2019;Shurrab et al, 2019;Støre-Valen and Buser, 2019, who found that a reduction of energy use contributed to environmental sustainability. Ajayi et al (2019), Chang and Devine (2019), and Ilhan and Banu Yobas (2019) also found that energy efficiency implementation reduces the impact on the environment, as well as producing local and global environmental benefits (Omer, 2014).…”
Section: Energy Management -> Environmentmentioning
confidence: 99%
“…Increasing consideration of embodied impacts of building materials is therefore expected of sustainable design appraisal systems such as BREEAM, as well as building regulations, as they remain the essential tools for driving sustainability in the built environment. This is especially important as a recent analysis by Ajayi et al (2019) suggests that sustainable design appraisal tools have not been doing enough to drive the required reduction in embodied energy of buildings.…”
Section: Implications For Practice and Policy Makingmentioning
confidence: 99%